Application of bilateral erector spinae plane block as a component of multimodal analgesia in pediatric practice: a case report - Glazov, Ye O (Pain medicine, 2021)
The article describes a clinical case of using a modified blockade of the back extensor muscle space as a component of postoperative multimodal analgesia in a toddler who was urgently operated on for extensive phlegmon of the anterior abdominal wall. This clinical case demonstrated the effectiveness of this method, and its use is quite simple in pediatric practice.